Bilateral Atypical Facial Pain Caused by Eagle’s Syndrome - V. Anuradha; Ravi Sachidananda; Satish Kumaran Pugazhendi; Preeti Satish; Romir Navaneetham (Case Reports in Dentistry)
Recurrent throat pain, “foreign body” sensation, difficulty in swallowing, or vague facial pain is many times caused by the presence of an elongated styloid process. Many times, this condition is misdiagnosed and the patient is treated for facial neuralgia. But once Eagle’s syndrome is confirmed by clinical and radiological examination, the treatment is always surgical resection. The approach maybe intraoral or extraoral. In this paper, we present a case of Eagle’s syndrome caused by bilateral elongation of the styloid process and where surgical resection of the same gave instant permanent relief for the patient.